2011
DOI: 10.3892/ijmm.2011.695
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory activities of Agelanthus dodoneifolius (Loranthaceae) extracts on stimulated equine neutrophils and myeloperoxidase activity

Abstract: Abstract. Agelanthus dodoneifolius DC Danser (Loranthaceae)is used for the treatment of various diseases including asthma. The aqueous and hydroalcoholic extracts have been reported to have anti-inflammatory, spasmolytic and bronchorelaxant activities. The present study investigates the effects of the aqueous decoction and the diethyl ether, ethyl acetate and butanolic fractions of Agelanthus dodoneifolius DC Danser (Loranthaceae) on reactive oxygen species (ROS) production and myeloperoxidase (MPO) release by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…When the half maximal inhibitory concentrations were compared, the inhibitory potency decreased in the following order: n -butanolic subfraction (IC 50 = 2.8 ± 1.2 μ g/mL) > gallic acid (IC 50 > 25 μ g/mL), data from previous work [ 13 ] ≥ ethyl acetate subfraction (IC 50 > 50 μ g/mL). Contrary to our study, Kroes et al [ 33 ] had previously reported an efficient inhibitory effect of gallic acid on MPO release by using another neutrophils activator: zymosan which was different in our model based on PMA stimulation.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…When the half maximal inhibitory concentrations were compared, the inhibitory potency decreased in the following order: n -butanolic subfraction (IC 50 = 2.8 ± 1.2 μ g/mL) > gallic acid (IC 50 > 25 μ g/mL), data from previous work [ 13 ] ≥ ethyl acetate subfraction (IC 50 > 50 μ g/mL). Contrary to our study, Kroes et al [ 33 ] had previously reported an efficient inhibitory effect of gallic acid on MPO release by using another neutrophils activator: zymosan which was different in our model based on PMA stimulation.…”
Section: Resultsmentioning
confidence: 74%
“…Recently we have shown that butanolic and ethyl acetate fractions of Agelanthus dodoneifolius exhibited excellent anti-inflammatory and antioxidant properties that were attributed to their polyphenol components [ 13 ]. However, these interesting activities were not properly correlated to a specific type of polyphenols contained in each tested fraction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations